2002
DOI: 10.4269/ajtmh.2002.67.578
|View full text |Cite
|
Sign up to set email alerts
|

Gambian children successfully treated with chloroquine can harbor and transmit Plasmodium falciparum gametocytes carrying resistance genes.

Abstract: Abstract. Polymorphisms in two genes of Plasmodium falciparum (P. falciparum multidrug resistance 1 [pfmdr1] and P. falciparum chloroquine [CQ] resistance transporter [pfcrt]) are associated with CQ treatment failure. We found significant linkage disequilibrium between these loci among isolates from symptomatic Gambian children (P ‫ס‬ 0.026) and strong selection for the resistance-associated alleles pfmdr1-86Tyr and pfcrt-76Thr in children with persistent or re-emerging P. falciparum trophozoites during post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 36 publications
6
103
2
1
Order By: Relevance
“…This relatively rapid change in allele frequency in vivo suggests a considerable fitness deficit may be associated with the mutant form of pfcrt in this region. There was no significant decrease in the frequency of the N86Y pfmdr1 mutation over the same seasonal intervals, supporting the hypothesis that mutations in pfcrt associated with CQ resistance may be more strongly affected by the presence or absence of drug pressure in vivo than the N86Y mutation in pfmdr1 [a polymorphism not investigated in this study, but one that several studies have shown to be linked to CQ resistance in Africa (Sutherland et al, 2002;Abdel-Muhsin et al, 2004)]. …”
Section: Discussionsupporting
confidence: 80%
“…This relatively rapid change in allele frequency in vivo suggests a considerable fitness deficit may be associated with the mutant form of pfcrt in this region. There was no significant decrease in the frequency of the N86Y pfmdr1 mutation over the same seasonal intervals, supporting the hypothesis that mutations in pfcrt associated with CQ resistance may be more strongly affected by the presence or absence of drug pressure in vivo than the N86Y mutation in pfmdr1 [a polymorphism not investigated in this study, but one that several studies have shown to be linked to CQ resistance in Africa (Sutherland et al, 2002;Abdel-Muhsin et al, 2004)]. …”
Section: Discussionsupporting
confidence: 80%
“…Extracted DNA was genotyped for Pfcrt-76Thr/Lys by PCR-restriction fragment length polymorphism using methods described previously (9,36).…”
Section: Methodsmentioning
confidence: 99%
“…Although acquired immune responses may be more important in drug-resistant infections, parasite genotypes were not determined. Mutations in the Pfcrt and Pfmdr1 genes are associated with resistance to chloroquine (CQ), but the Pfcrt-76Thr variant appears most strongly associated with CQ resistance in all populations examined so far (9,36,38). In addition, in Malawi, the prevalence of the Pfcrt76Thr variant decreased in the parasite population after CQ treatment was discontinued, while that of the Pfmdr1-86Tyr variant remained unchanged (28).…”
mentioning
confidence: 99%
“…Evidence in favor of this includes the following: (i) these mutations segregate with CQR in a P. falciparum genetic cross (17)(18)(19); (ii) mutant pfcrt haplotypes show an excellent association with CQR in laboratory-adapted field isolates from multiple geographically distinct regions (19 -21); (iii) pfcrt point mutations are often associated with an increased risk of CQ treatment failure (21)(22)(23)(24); (iv) microsatellite markers support a recent, worldwide sweep of mutant pfcrt haplotypes under CQ pressure (25); and (v) allelic exchange data have recently provided conclusive evidence that mutant pfcrt alleles prevalent in Asia, Africa, South America, and the Oceanic region can confer CQR to a CQ-sensitive (CQS) clone (26).…”
mentioning
confidence: 99%